The role of lumateperone in the treatment of schizophrenia - Alveena Batool Syed; James Robert Brašić (SAGE Publishing, 2021)
Schizophrenia is a devastating mental disorder resulting in marked morbidity and mortality despite the optimal use of all currently available interventions. For this reason, the release of lumateperone (Captyla R ), also known as ITI-007, an orally administered, atypical antipsychotic provided a welcome novel tool for clinicians to utilize precision medicine to tailor an optimal treatment plan to the specific needs of each person with schizophrenia. To generate a foundation for clinicians to assess the risks and benefits of lumateperone in relation to other interventions for schizophrenia, we conducted a search of items for 'ITI-007' and 'lumateperone' on PubMed, ScienceDirect, Web of Science, Google Scholar, and www.clinicaltrials.gov . We present a critical evaluation of the limited information about lumateperone for schizophrenia, its use approved by the US Food and Drug Administration. Lumateperone merits consideration for patients with treatment-resistant schizophrenia and for patients with schizophrenia who are vulnerable to developing metabolic dysfunction and movement disorders. On the other hand, lumateperone should not be used for (a) women who are pregnant or breastfeeding, children, adolescents, and elderly patients with dementia-related psychosis, (b) patients who are at risk for cerebrovascular diseases, (c) patients who use inducers and moderate or strong inhibitors of the cytochrome P450-3A4 (CYP3A4) isozyme, and (d) patients who use alcohol and other sedating agents. Clinical trials from multiple centers without financial conflicts of interest to market lumateperone are needed to directly compare and contrast lumateperone and other antipsychotic agents to generate trustworthy evidence to be assessed objectively by clinicians treating patients with schizophrenia. Future investigations will provide the foundations to identify the evidence for comprehensive evaluations of the role of lumateperone in the treatment of people with schizophrenia and other conditions.